Comparison of meat quality and various clinical parameters from pigs in free-range husbandry - Küper, Johanna; Frölich, Kai; Stäbler, Rupert; Jaeger, Wilhelm; Junkmann, Dennis; Upmann, Matthias; Schaubmar, Andreas R.; Kehrenberg, Corinna (Tierärztliche Praxis Ausgabe G: Großtiere / Nutztiere, 2025)
The aim of this study was to compare the fattening performance and pork quality of 10 pigs from the endangered breed Bentheim Black Pied (BBS) with 30 F1 pigs from the widely used Danish hybrid pig (Large White x Danish Landrace) crossed with BBS (BHP), all fattened up under free-range conditions.A total of 40 pigs were fattened up under a restrictive feeding regime on a 1.28ha pasture and weighed monthly. Subsequently, the pigs were slaughtered, carcass traits were assessed, and samples from M. longissimus thoracis et lumborum (LTL) and back-fat were collected for laboratory analysis.Fattening performance differed significantly between the groups: BHP pigs were significantly heavier at the end of the fattening period (128.3 kg BHP vs. 102.5 kg BBS), with significantly higher average daily weight gain. Significant differences were observed in carcass characteristics (carcass length, cutlet weight, carcass yield). However, BBS pigs showed a more favourable fatty acid profile, notably with higher levels of the essential α-linolenic acid. Water-holding capacity was lower in BHP pigs, with significantly higher drip losses during cold storage at 2°C, while grill- and thawing-losses did not differ significantly. Sensory analysis revealed that untrained panellists were able to distinguish between meat of both groups. BBS meat was rated as more tender, which was also confirmed by significantly lower shear force measurements.The study showed that crossbreeding BBS and Danish hybrid pigs can compensate for performance deficits of the traditional breed -such as slower growth- while partially retaining beneficial traits, such as a nutritionally superior fatty acid composition. Overall, the results are in line with the expectations for F1 crossbred pigs, when 2 breeds with different performance parameters are used. These findings are relevant for veterinary practitioners involved in sustainable pig production, the conservation of rare breeds, and the development of alternative outdoor husbandry systems.
Keywords: Carcass quality; outdoor pig production; sensory meat characteristics; fatty acid composition; pig fattening